PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU PADA SD SWASTA TALITAKUM MEDAN - Kevin Julinco Butar Butar; Luter Girsang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to examine the influence of principal leadership and work motivation on teacher performance at Talitakum Medan Private Elementary School. This research uses quantitative methods, the population used is 23 people and uses a purposive sampling method, with the aim of obtaining a representative sample according to the criteria set in the research. Data collected through questionnaires, interviews and books and other journals. The results of this study indicate that in particular the principal's leadership has a positive and significant effect on teacher performance, work motivation has a positive and significant effect on teacher performance inTalitakum Medan Private Elementary School. In conclusion, there is a positive and significant influence on teacher performance.